Adaptation Atlas SpatioTemporal Asset Catalog (STAC) - Youngberg, Brayden; Steward, Peter Richard; Rosenstock, Todd Stuart (2025)
The Agriculture Adaptation Atlas utilizes a SpatioTemporal Asset Catalog (STAC) to support its vision of being an accessible and collaborative tool for sharing and creating data and data stories for decision-makers. The STAC spec is a collection of metadata standards used to represent spatial data using JSON files. By cataloging that Adaptation Atlas data within a STAC, we ensure accessibility and usability by following an established and widely adopted community standard. This ensures that datasets are discoverable, and easy to use across spatial tools and programming environments, and enables efficient searching, filtering, and querying of data while promoting collaboration and reuse. The datasets cataloged within the STAC are stored in Cloud-optimized formats, such as COG and Parquet, to further allow efficient querying and discovery of data by allowing users to download information for specific layers or regions of interest, rather than the full datasets.